NARSISTIK EKSTRAVERSI AGEN AMY DUNNE SEPERTI YANG TERLIHAT DALAM FILM "GONE GIRL" OLEH DAVID FINCHER - Rifqi, Ahmad; Widyahening, Ch. Evy Tri (ENGLISH RESEARCH JOURNAL, 2024)
The objective of this research was to analyze the agentic extraversion narcissistic traits exhibited by the main character, Amy Dunne, as seen in the movie "Gone Girl," directed by David Fincher. The researcher used a descriptive-qualitative methodology. The data were collected through the use of documentation, including watching the movie, reading the script, and taking notes. In analyzing the data, the researcher used an interactive approach to data analysis, as defined by Miles and Huberman, which included the following stages: data collection, data reduction, data display, and drawing conclusion verification. This approach was used to ensure the validity of the research. Additionally, the researcher employed a triangulation of data and triangulation theory to enhance the rigor of the research. The findings of this research indicate that the agentic extraversion narcissistic traits exhibited by the main character, Amy Dunne's, are: achieved goals and influenced by fame, as seen in the movie Gone Girl. Keyword : Narcissistic, Gone Girl Movie, Descriptive Qualitative